Surgical strategy for purulent-septic complications of combat abdominal trauma - O. Herasymenko; M. Kashtalian; Ya. Haida; A. Okolets; P. Shkliarevych; D. Atanasov (Kazimierz Wielki University, 2023)
The incidence of combat abdominal trauma ranges from 6.7 to 9%. The nature of gunshot abdominal wounds leads to the development of functional disorders and complications (51-81%) and, as a result, a high mortality rate (12-31%). The purpose of the work is to improve the effectiveness of surgical treatment of purulent-septic complications in wounded patients with combat abdominal trauma (CAT). We analysed the treatment of 86 wounded patients with purulent-septic complications of CAT who were hospitalized at the Military Medical Clinical Centre of the Southern Region. Taking into account the location, clinical manifestations and severity of the injury, modern methods of treatment were used, namely: puncture-drainage interventions under ultrasound guidance and the NPWT system installation. The complex treatment was supplemented with antibacterial therapy and oxygen barotherapy. First of all, the wounded patients underwent US-guided puncture, drainage interventions and stage debridement for diagnostic and therapeutic purposes. NPWT therapy was used in 11 patients with large wounds and purulent-septic complications of the soft tissues of the anterior abdominal wall. So, the use of interventional ultrasound as a priority diagnostic and therapeutic method for purulent and inflammatory complications of combat abdominal trauma improved the quality of diagnosis and reduced the number of traumatic interventions, which led to a decrease in postoperative complications and the duration of inpatient treatment. 11 (14.2%) cases of puncture-drainage interventions were ineffective, and therefore it was necessary to use traditional methods of treatment - opening and draining purulent-inflammatory foci and using NPWT therapy. Vacuum therapy is an effective method of treating purulent-septic complications of gunshot wounds of the abdominal soft tissues, which, in combination with puncture-drainage interventions, can 2.5 folds reduce the number of recurrent operations (mainly multistage surgical procedures), thereby 1.8 folds reducing the length of hospital stay. The use of current methods has improved the results of surgical treatment of purulent-septic complications in wounded patients with purulent-septic complications of combat abdominal trauma. The use of the current techniques helped to reduce the number of invasive treatment methods, facilitated recovery, reduced bed days, reduced intoxication, and increased the percentage of recovered military personnel.